The Impact of Human Resource Practices on Shareholder Value - Wibowo, Padmono (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aims to measure the specific impact of various human resource management (HRM) practices on shareholder value and identify the most effective HRM strategies for enhancing this value. Employing a comprehensive empirical analysis, the research integrates HR and financial data across diverse industries and organizational contexts to evaluate HRM's contribution to corporate financial performance. The methodology includes an extensive literature review, secondary data collection from scholarly articles, industry reports, and semi-structured interviews with HR managers and corporate leaders. Data analysis utilizes open and axial coding techniques from grounded theory to uncover patterns and relationships between HRM practices and shareholder value. Findings indicate that effective HRM practices, such as robust recruitment, continuous employee development, and performance-based incentive systems, significantly correlate with improved financial performance, particularly regarding return on assets (ROA) and market value added (MVA). The effectiveness of these HRM practices is highly context-dependent, with high-tech sectors benefiting more than traditional manufacturing. Aligning HRM strategies with organizational goals, internal culture, and strong leadership support is crucial for optimizing HRM's impact on financial outcomes. The study suggests integrating comprehensive measurement metrics and exploring digital technology's role in HRM as future research directions. This research underscores the importance of HRM as a core component of business strategy to enhance shareholder value.